Diminished Blood Pressure Profiles in Children With Down Syndrome. Issue 3 (March 2020) - Santoro, Jonathan D.; Lee, Sarah; Mlynash, Michael; Mayne, Elizabeth W.; Rafii, Michael S.; Skotko, Brian G.
Abstract : This study sought to analyze blood pressure trends in children with Down syndrome at multiple centers. A multicenter, retrospective, cross-sectional study was performed. All patients were <18 years and had a diagnosis of Down syndrome. Existing comorbidities were nonexclusionary. For each patient, 3 blood pressure recordings were obtained from routine clinic visits. In total, 887 patients with 2661 total blood pressure recordings were included in this study. The average blood pressure percentile for patients was 38.87 with a median percentile of 31.5. Age, sex, and race were not predictive of blood pressure percentile. Compared with established data from the National Heart Lung and Blood Institute and National Health and Nutrition Examination Survey cohort (ages 8–18 years), blood pressure in our Down syndrome population was statistically lower by 6.1 percentile points ( P <0.001), with the greatest difference at higher blood pressure percentiles ( P <0.001). Only 10% of all Down syndrome cohort blood pressure recordings were greater than the National Heart Lung and Blood Institute/National Health and Nutrition Examination Survey 70th percentile, with no patients meeting criteria for prehypertension or hypertension. Additional comparisons against American Academy of Pediatrics data were similar and statistically significant. In children with Down syndrome, there is a 12 percentile point reduction in baseline blood pressure compared with age- and height-matched controls reported in the National Heart Lung and Blood Institute/National Health and Nutrition Examination Survey and American Academy of Pediatrics cohorts. This data can potentially be utilized in the evaluation and care of persons with Down syndrome in their pediatric medical homes. Abstract : Supplemental Digital Content is available in the text.